The Use of Telehealth in School-Based Health Centers - Hayley Love PhD, MSc; Nirmita Panchal MPH; John Schlitt MSW; Caroline Behr BA; Samira Soleimanpour PhD, MPH (SAGE Publishing, 2019)
Telehealth is a growing model of delivering health care. School-based health centers (SBHCs) provide access to health care for youth in schools and increasingly use telehealth in care delivery. This article examines the recent growth of telehealth use in SBHCs, and characteristics of SBHCs using telehealth, including provider types, operational characteristics, and schools and students served. The percentage of SBHCs using telehealth grew from 7% in 2007-2008 to 19% in 2016-2017. Over 1 million students in over 1800 public schools have access to an SBHC using telehealth, which represents 2% of students and nearly 2% of public schools in the United States. These SBHCs are primarily in rural communities and sponsored by hospitals. This growing model presents an opportunity to expand health care access to youth, particularly in underserved areas in the United States and globally. Further research is needed to fully describe how telehealth programs are implemented in school settings and their potential impacts.